Editorial. Issue 1 (March 2016) - Waldron, L.
Abstract : First of all, happy 2016 to all, even through by the time this is published we will be three months into the New Year. The world of poultry science continues to be challenged with various issues, competition for feed raw materials with the human population, the changes in weather due to El Niňo, and so research has to continue into finding novel solutions to evolving problems. The current issue covers various topics including immunity, alternative raw materials for feed, welfare, behaviour, disease, genetics and breeding. 2015 saw a backlog of papers cleared where we were waiting for author revisions, allowing us to increase our turnaround time, although we still sometimes struggle to find suitable reviewers for more obscure topics – so please consider reviewer suggestions carefully if you're submitting such as paper. This year is a World Poultry Congress year - this time hosted by the Chinese Branch in Beijing. I am reliably informed that preparations are well under way – so I look forward to seeing a lot of new information and having the opportunity to get more review papers published from this event. Check out the WPSA.com website for details in submitting papers for this key event. I shall also be attending the WPSA UK event in Chester England in April, as part of my annual end of tax year meetings with publishers and hope to see various poultry scientists there. So here's to a productive and informative 2016, and do submit your reviews on any topic related to poultry. If you have any queries regarding publishing – do get in contact as we are happy to help! Dr Lucy Waldron Editor